Stress Response Of Polytene Chromosomes Of Sarcophaga Ruficornis (Fab.) (Sarcophagidae: Diptera) To Lead Nitrate - AKANKSHA SINGH,; RASHMI SINGH,; UMA R. AGRAWAL,; R.R. TEWARI, (International Journal of Pharma and Bio Sciences, 2012)
Stress response to lead nitrate was analyzed in polytene chromosomes of the pupal foot pad cells of flesh fly Sarcophaga ruficornis. At different concentrations and time intervals only a single large puff was induced at region 12A of the chromosome arm II L.The same puff is known to be induced by heat shock and chemical stress in several sarcophagids. Thus the induction of this puff in sarcophagids may be used as a biomarker for assessment of genotoxicity.